Review Paper: Use of Vetiver (Vetiveria zizanoides L.) and Rice Husk Biochar in Remediation of Mercury (Hg) Polluted Soil - Baiq Siti Rohmaniati; Taufik Fauzi; A. A. Ketut Sudharmawan; Suwardji (Jurnal Biologi Tropis, 2023)
Indonesia has abundant natural resources. One of the great natural resources is mineral resources in the form of gold. With this potential, the number of national mining locations continues to increase, both large, medium, small and unlicensed gold mining (PETI) carried out directly by the community, either in groups or individually, which can have a negative impact on the environment. pollution such as land and water. , because the results of gold processing which contain heavy metals (Hg) are immediately thrown away without any further processing. This can harm the surrounding environment and even enter the food chain. Therefore, the purpose of this paper is to study and find out related information regarding the effectiveness of phytoremediation of soil contaminated with heavy metals such as mercury (Hg) using vetiver (Vetiveria zizanoides L.) and soil ameliorant materials in the form of rice husks. biochar to reduce the concentration of these heavy metals, as well as the mechanisms involved in phytoremediation of soil contaminated with heavy metals. The vetiver root plant (Vetiveria zizanoides L) is very effective for use in remediating soil contaminated with mercury (Hg) or other heavy metals. The use of biochar can influence the growth and absorption of heavy metals by vetiver (Vetiveria zizanoides L). Biochar is also able to improve the physical and chemical properties of soil and stabilize heavy metals in the soil.